Changes in End-User Petroleum Product Prices : A Comparison of 48 Countries - Kojima, Masami (World Bank, Washington, DC, 2014)
This paper presents retail prices of the petroleum products in August 2008 in up to 56 countries, and examines the degree of pass through to consumers of increases in world gasoline and diesel prices since January 2004 in 48 countries. This is the second paper in a series summarizing work undertaken to assess the implications of higher oil prices on fuel use, the downstream petroleum sector, and household fuel consumption in the developing world. It follows a recent publication on a decomposition analysis of vulnerability to oil price increases, where vulnerability is defined as the percentage of gross domestic product (GDP) spent on net imports of crude oil and petroleum products (Bacon and Kojima 2008). This paper focuses on the extent to which international petroleum product price increases have been passed on to consumers.